A Two Phase Ultrasound Image De-speckling Framework by Nonlocal Means on Anisotropic Diffused Image Data - Thakur, Niveditta; Khan, Nafis Uddin; Sharma, Sunil Datt (Informatica, 2023)
Image de-speckling is one of the most challenging issues in multimedia imaging systems. All the available speckle noise reduction filters are almost capable of noise reduction but failed to restore the subtle features such as low gray level edges and fine details under the poor contrast background. This paper presents a two phase ultrasound image de-speckling framework by utilizing the capability of non-local mean filtering method for de-speckling and edge preservation on anisotropic diffused images. The prior image smoothing along with edge preservation and contrast enhancement by anisotropic diffusion is carried out in first phase which is then followed by non-local means method for de-speckling and edge sharpening in the next phase. The degree of attenuation of speckle noise is evaluated on low contrast standard and ultrasound images and the results are compared with state-of-the-art and advanced anisotropic diffusion techniques and non-local means methods. The experimental analysis demonstrates the capability of proposed method in reducing the noise and preserving the edges better than the available speckle reduction filters.